OPTIMIZATION OF ISLAMIC RELIGIOUS EDUCATION TEACHERS' COMPETENCE IN THE ERA OF SOCIETY 5.0 - Diana, Ridma (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2025)
The Society 5.0 era, characterized by rapid technological and human-centered advancements, has transformed various sectors, including education. This article discusses the importance of optimizing the competencies of Islamic Religious Education (IRE) teachers to face the challenges of this new era. The study employs a thematic systematic literature review method, analyzing seven relevant articles published within the last five years. The findings reveal that IRE teachers are expected to strengthen their pedagogical, personal, social, and professional competencies as mandated by Indonesian Law No. 14 of 2005. Furthermore, teachers must also develop 21st-century skills, specifically the 4C competencies: Critical Thinking, Creativity, Collaboration, and Communication. These competencies are essential for fostering innovative, interactive, and student-centered learning environments aligned with the needs of the Society 5.0 era. The article concludes that the success of educational transformation in the digital age largely depends on the readiness and adaptability of teachers, particularly IRE educators, in integrating technology and soft skills into their teaching practices. Strengthening these competencies will not only enhance the quality of education but also contribute to shaping students with strong moral character and the ability to face future challenges.